Saving Face in Front of the Computer? Culture and Attributions of Human Likeness Influence Users' Experience of Automatic Facial Emotion Recognition - Stein, Jan-Philipp; Ohler, Peter (Frontiers in Digital Humanities, 2018)
In human-to-human contexts, display rules provide an empirically sound construct to explain intercultural differences in emotional expressivity. A very prominent finding in this regard is that cultures rooted in collectivism—such as China, South Korea, or Japan—uphold norms of emotional suppression, contrasting with ideals of unfiltered self-expression found in several Western societies. However, other studies have shown that collectivistic cultures do not actually disregard the whole spectrum of emotional expression, but simply prefer displays of socially engaging emotions (e.g., trust, shame) over the more disengaging expressions favored by the West (e.g., pride, anger). Inspired by the constant advancement of affective technology, this study investigates if such cultural factors also influence how people experience being read by emotion-sensitive computers. In a laboratory experiment, we introduce 47 Chinese and 42 German participants to emotion recognition software, claiming that it would analyze their facial micro-expressions during a brief cognitive task. As we actually present standardized results (reporting either socially engaging or disengaging emotions), we manipulate participants’ impression of having matched or violated culturally established display rules in a between-subject design. First, we observe a main effect of culture on the cardiovascular response to the digital recognition procedure: Whereas Chinese participants quickly return to their initial heart rate, German participants remain longer in an agitated state. A potential explanation for this—East Asians might be less stressed by sophisticated technology than people with a Western socialization—concurs with recent literature, highlighting different human uniqueness concepts across cultural borders. Indeed, while we find no cultural difference in subjective evaluations of the emotion-sensitive computer, a mediation analysis reveals a significant indirect effect from culture over perceived human likeness of the technology to its attractiveness. At the same time, violations of cultural display rules remain mostly irrelevant for participants’ reaction; thus, we argue that inter-human norms for appropriate facial expressions might be loosened if faces are read by computers, at least in settings that are not associated with any social consequence.